Disciplinamento e humanização: a formação policial militar e os novos paradigmas educacionais de controle e vigilância - França, Fábio Gomes de (2012)
This work intends to analyze the contradiction between new educational paradigms and disciplining on the military police trainning in Paraiba. Its hypothesis is that the humanizing discourse used during the socialization of new policial officers actually hide a control and surveillance process as a new power strategy. The relation between discipline and power is analyzed through an historical analysis of the implementation of human Rights courses on the police training center. In this way, aiming to create a new image for itself, Military Police in Paraiba developed a citizenship based discourse about its practices through a new curriculum and courses, mosaics and panels displaing its ideals around the headquarter. This research shows empirically how supposedly humanists new knowledges and discourses employed by military police is actually pait of a new control mechanisms used to develop social order. The research tries to clarity why and how Human Rights teaching actually develop forms of resistance among new officers and the belief that it is only an instrument to protect criminals. Our hypothesis is that the very teaching process of Human Rights on the training center, due to its military and disciplining roots, avoids an understanding of the its necessity.